Pengaruh Ukuran Perusahaan, Profitabilitas dan Solvabilitas terhadap Nilai Perusahaan pada Perusahaan Manufaktur Subsektor Makanan dan Minuman di Bursa Efek Indonesia Tahun 2019-2021 - Lewi Patabang; Rahmawati Fitriana; Friska Efriyanti Manurung (Jurnal EKSIS, 2023)
Abstract The main goal of a company is to maximize prosperity for stakeholders and can be achieved by maximizing company value. This research aims to determine and analyse the influence of company size, profitability and solvency on company value in food and beverage subsector manufacturing companies on the IDX listed in 2019-2021. The data used is secondary data which is the 2019-2021 financial report from the Indonesia Stock Exchange. The research population was 14 companies selected using a purposive sampling method with certain criteria. Data analysis techniques were carried out using descriptive statistical tests, classical assumption tests, multiple linear regression tests. The research results show that the two dependent variables (profitability and solvency) have a significant effect on company value, however company size does not have a significant effect on company value. Simultaneously, company size, profitability and solvency have an effect on company value.